Production of structurally diverse wheat arabinoxylan hydrolyzates using combinations of xylanase and arabinofuranosidase. (5th November 2015) - Mendis, Mihiri; Simsek, Senay
Highlights: Arabinoxylan hydrolyzates (AXH) were generated using enzymatic hydrolysis. Aspergillus niger xylanase produce AXH with simple structural details. Cellvibrio japonicas xylanase produce AXH with more complex structural details. The information could be useful in generating AXH with desired structural details. Abstract: Structurally different wheat arabinoxylan hydrolyzates (AXH) were generated using different combinations of Cellvibrio japonicas xylanase (CJX), Aspergillus niger xylanase (ANX), Bifidobacterium adolescentis arabinofuranosidase (BAF) and Clostridium thermocellum arabinofuranosidase (CAF). Between the two xylanases, ANX might be an enzyme of choice for the production of AXH with simple structural details while CJX might be selected for the production of AXH with more complex structural features. Addition of BAF followed by CAF is more effective in generating AXH with higher amount of unsubstituted xylose. CJX series resulted in lower molecular weights compared to ANX series. The information derived about the capabilities of the two xylanases and two arabinofuranosidase could provide important information in decision making regarding enzymes to be used to generate AXH with specific structural details. Such hydrolyzates could be useful as substrate for future research exploring the effect of fine structural details in AXH on their biological and physical properties.